NETWORK KPI ANALYSIS IN NETWORK SHARING TECHNOLOGY CONFIGURATION BASED ON MULTI-OPERATOR CORE NETWORK (MOCN) - Widiantoro, Andreas Gunawan; Tjahjamooniarsih, Neilcy; Marpaung, Jannus; Kusumawardhani, Eka; Ade Putra, Leonardus Sandy (Faculty of Engineering, Universitas Tanjungpura, 2023)
The reliable spread of BTS networks with high system capacity poses a challenge for operators in delivering services. An alternative strategy is network sharing, one of which is MOCN (Multi Operator Core Network). MOCN BTS is configured to share RF module and antenna resources by combining frequencies between operators while maintaining each operator's core. On the other hand, BTS not-pair is the conventional operator configuration where RF modules and antennas are installed independently without any connection to other operators. In this final project, a KPI data analysis is conducted for both BTS configuration to assess their reliability. Four BTS samples from two operators (IM3 and 3ID) are taken for this analysis. The analyzed KPI categories include Accessibility KPI, Retainability KPI, and Service Integrity KPI during busy hours. KPI data is obtained from field results and assisted by the technical team from Indosat Ooredoo Hutchison Pontianak. The analysis results indicate that in terms of Service Integrity KPI, BTS MOCN outperforms BTS not-pair, with a difference of 2.590175 Mbps for downlink and 0.286065 Mbps for uplink. Regarding Accessibility KPI and Retainability KPI, BTS managed by 3ID demonstrates better performance compared to those managed by IM3.